2020
DOI: 10.3390/pr8040442
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model Based on the Shape of Pulse Waves Measured at a Single Spot for the Non-Invasive Prediction of Blood Pressure

Abstract: Background: Continuous non-invasive blood pressure (BP) measurement is a desired virtue in clinical practice. Unfortunately, current systems do not allow one for continuous, reliable BP measurement for more than a few hours per day, and they often require a complicated set of sensors to provide the necessary biosignals. Therefore we investigated the possibility of proposing a computational model that would predict the BP from pulse waves recorded in a single spot. Methods: Two experimental circuits were create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…From Table 1, it can be observed that the proposed tool had, on average, a sensitivity (SE) of 100%, a positive predictive value (PPV) greater than 99 %, and an F1 score greater than 99 % for the detection of all key points within a cardiac cycle in both ABP and PPG waveforms. The tool utilizes a single signal (the non-stationary component of the IEM method) to identify the temporal location of all key points within a cardiac cycle, in contrast to the two different signals employed in the literature (1 st and 2 nd derivatives) [15]. Moreover, in terms of computational cost, the IEM method requires only O (LN) operations for number of iterations L and signal length of N. The graphical user interface we designed to help researchers and clinicians use our proposed tool is shown in Fig.…”
Section: A Key Points Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 1, it can be observed that the proposed tool had, on average, a sensitivity (SE) of 100%, a positive predictive value (PPV) greater than 99 %, and an F1 score greater than 99 % for the detection of all key points within a cardiac cycle in both ABP and PPG waveforms. The tool utilizes a single signal (the non-stationary component of the IEM method) to identify the temporal location of all key points within a cardiac cycle, in contrast to the two different signals employed in the literature (1 st and 2 nd derivatives) [15]. Moreover, in terms of computational cost, the IEM method requires only O (LN) operations for number of iterations L and signal length of N. The graphical user interface we designed to help researchers and clinicians use our proposed tool is shown in Fig.…”
Section: A Key Points Detectionmentioning
confidence: 99%
“…These medical applications of PPG and ABP features clearly emphasize the importance of accurately detecting all five key points within a cardiac cycle in these waveforms, as they form the foundation for feature extraction and subsequent clinical applications. The use of derivatives (1 st and 2 nd ) of ABP and PPG waveforms is a common method for detecting key points within a cardiac cycle in these waveforms [15]. However, the sensitivity of signal derivatives to noise presents a significant challenge for accurate detection of these key points, potentially resulting in the extraction of inaccurate features.…”
Section: Introductionmentioning
confidence: 99%
“…Many different algorithms have been developed to detect the DN [6,7,25,26,27,28,29,30]. However, either these methods were not thoroughly tested for noise robustness, or they were not examined for their ability to identify the DN in signals lacking a prominent notch (DN-less signals).…”
Section: Introductionmentioning
confidence: 99%
“…However, either these methods were not thoroughly tested for noise robustness, or they were not examined for their ability to identify the DN in signals lacking a prominent notch (DN-less signals). Among these methods the 2 nd derivative method is the most widely used method for DN detection in the literature [28,31,32]. This approach employs the e-peak, the third peak within the 2 nd derivative of the PPG cardiac cycle, to estimate the DN within the cardiac cycle [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation